Plasmodium falciparum encodes a conserved active inhibitor-2 for Protein Phosphatase type 1: perspectives for novel anti-plasmodial therapy - Fréville, Aline (BioMed Central, 2013)
BACKGROUND: It is clear that the coordinated and reciprocal actions of kinases and phosphatases are fundamental in the regulation of development and growth of the malaria parasite. Protein Phosphatase type 1 is a key enzyme playing diverse and essential roles in cell survival. Its dephosphorylation activity/specificity is governed by the interaction of its catalytic subunit (PP1c) with regulatory proteins. Among these, inhibitor-2 (I2) is one of the most evolutionarily ancient PP1 regulators. In vivo studies in various organisms revealed a defect in chromosome segregation and cell cycle progression when the function of I2 is blocked. RESULTS: In this report, we present evidence that Plasmodium falciparum, the causative agent of the most deadly form of malaria, expresses a structural homolog of mammalian I2, named PfI2. Biochemical, in vitro and in vivo studies revealed that PfI2 binds PP1 and inhibits its activity. We further showed that the motifs (12)KTISW(16) and (102)HYNE(105) are critical for PfI2 inhibitory activity. Functional studies using the Xenopus oocyte model revealed that PfI2 is able to overcome the G2/M cell cycle checkpoint by inducing germinal vesicle breakdown. Genetic manipulations in P. falciparum suggest an essential role of PfI2 as no viable mutants with a disrupted PfI2 gene were detectable. Additionally, peptides derived from PfI2 and competing with RVxF binding sites in PP1 exhibit anti-plasmodial activity against blood stage parasites in vitro. CONCLUSIONS: Taken together, our data suggest that the PfI2 protein could play a role in the regulation of the P. falciparum cell cycle through its PfPP1 phosphatase regulatory activity. Structure-activity studies of this regulator led to the identification of peptides with anti-plasmodial activity against blood stage parasites in vitro suggesting that PP1c-regulator interactions could be a novel means to control malaria.